After the Ten Commandments … the Sermon?: Comments on David Labaree’s Research Recommendations - M. Depaepe (Between Educationalization and Appropriation, 2012)
It was bound to happen. After some supposed authority boldly announces ten commandments for good research practices in his domain (Depaepe, 2010), another one suddenly pops up – in this case a ‘real’ authority – who cannot resist the urge to give a sermon on almost the same subject (Labaree, 2011). The historical but often repressed relationship between theology and pedagogy, repeatedly trumpeted by people like Fritz Osterwalder (2003), must have stuck in the subconscious of the historians of education. The religious metaphors prompted by the discussion about our opinion article (and which will undoubtedly resurface in comments on Labaree’s